(untitled) (MMIT Proceedings, 2024)
In this article, the author analyses the main trends in modern political pedagogy. Using specific examples, the author demonstrates the relevance of this field of education and its current trends, highlighting their unique aspects. It is demonstrated that these trends reflect the desire of political education to adapt to the changing conditions of the world.